2016
DOI: 10.12816/0031216
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mental Health among Iranian Medical Students : A Cross-Sectional Study

Abstract: Abstract:Objectives: More mental morbidities were reported in medical students than their nonmedical peers, which may negatively influence their lives and future career. The aim of this study was to assess the mental health status among medical students of Shiraz University of Medical Sciences. Method:Two hundred and eight 1 st to 4 th year Medical students took part in this cross-sectional study. General Health Questionnaire with 28 items (GHQ-28) was used for data collection. We performed descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 20 publications
12
39
0
1
Order By: Relevance
“…Assessment of psychological morbidity or mental health status of the respondents using the GHQ12 was a key finding in this study. The prevalence of psychological morbidity was 66.76%.This was found to be high compared to other studies [18,19,22,23]. However, studies conducted among medical students in Australia, England and Malaysia, which used the same cut off as the present study, showed comparable results as observed in the present study [14,24,25] Table 2.…”
Section: Mental Health Statussupporting
confidence: 78%
See 1 more Smart Citation
“…Assessment of psychological morbidity or mental health status of the respondents using the GHQ12 was a key finding in this study. The prevalence of psychological morbidity was 66.76%.This was found to be high compared to other studies [18,19,22,23]. However, studies conducted among medical students in Australia, England and Malaysia, which used the same cut off as the present study, showed comparable results as observed in the present study [14,24,25] Table 2.…”
Section: Mental Health Statussupporting
confidence: 78%
“…The reason behind this remains unclear. However, other studies reported contrary results which indicated associations with year level [22,23,[37][38][39].…”
Section: Mental Health Statusmentioning
confidence: 96%
“…Previous studies report varying relationship between female gender and depression. Some studies [ 10 , 13 ] show higher prevalence in female students while other studies [ 11 , 12 , 14 ] show no difference. High prevalence of depression seen in female medical students has been linked to personality traits [ 34 ], gender inequity and associated stigma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor mental health among medical students has been reported from various parts of Asia including India [ 10 – 12 ], Pakistan [ 13 ], Iran [ 14 ], Malaysia [ 15 ], China [ 16 ] and Saudi Arabia [ 4 ]. Poor mental health is found to be associated with serious thoughts of dropping out of medical school [ 17 ], substance abuse [ 18 ], burnout and suicidal ideation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical student begin with premedical year, students at this level were at higher stress because of the undeveloped coping skills (10) . Medical students in general have to read a condense materials, and most of this important material is in 3rd and 4th year so students at this periods were found to be more anxious (11) Medical student transition from basic science to clinical years was yet another factor that contributed to their stress. Other study found that first clinical year (year5) Students were more stressed than the second clinical year (year6) (12) .…”
mentioning
confidence: 99%